Development and characterization of confocal sputtered piezoelectric zinc oxide thin film. (February 2021) - Sharma, Pallavi; Guler, Zeynel; Jackson, Nathan
Abstract: Thin film zinc oxide (ZnO) is often used as a piezoelectric material, but its material properties are dependent on the deposition method and parameters. Direct sputtering using reactive DC or RF sputtering are the most common deposition methods for thin film piezoelectric ZnO. This paper investigates the influence of varying sputtering parameters on piezoelectric and mechanical properties of ZnO deposited by confocal sputtering using pulsed DC on a silicon substrate. Parameters such as varying power, duty cycle and temperature were examined. Crystallinity of the films were investigated systematically by X-ray Diffraction. Mechanical properties such as hardness and Youngs Modulus of thin films were measured via nanoindentation. Piezoelectric coefficient d33 was also measured for the films. Results demonstrated that the ZnO thin film exhibited high c-axis (002) textured films with rocking curve full width half maximum values of 1.69°. It was observed that power, duty cycle and temperature significantly affected the crystallinity, mechanical properties and d33 values of the ZnO thin film. This paper demonstrates that pulsed DC confocal sputtering can be utilized to deposit piezoelectric ZnO films and demonstrates key sputtering parameters that influence the piezoelectric, mechanical and morphology properties of the film. Highlights: ZnO thin film deposited by confocal sputtering using DC, RF and Pulsed DC powers. Pulsed DC demonstrated better film quality in comparison to DC and RF. Identified key deposition parameters that effect film quality. Increased piezoelectric response for 40% duty cycle with high sputtering power.